Selection of optimal technical solutions for thermal modernization of school buildings - Maksymov, A.; Vakhovych, A. (Ways to Improve Construction Efficiency, 2020)
Analysis of the most common design and technological solutions used in thermal modernization, showed the impossibility of choosing the optimal solution for a single enclosing structure only by direct assessment of physical, mechanical and technical and economic characteristics. It is proposed to select the optimal design and technological solution in thermal modernization projects from all possible in two stages. At the first stage, it is necessary to discard those solutions, the implementation of which for this type of building is technically impossible or economically or technically impractical. In the second - to assess the system of indicators that comprehensively characterize the design and technological solution. In the article, based on the analysis of literature sources and the authors’ own experience in the development and maintenance of thermal modernization projects, a system of criterion evaluation for structural and technological solutions of thermal modernization is developed. The criterion evaluation system for structural and technological solutions of thermal modernization contains a number of indicators that take into account the physicochemical properties of the insulation, environmental friendliness, reliability and stability of the insulation system, technological factors such as maintainability, seasonality, high quality of work due to system technology, ability to sound insulation, economy, artistic efficiency. The method of expert evaluations for each criterion and sub-criterion determines its weight in the overall evaluation. The system of evaluation of technical decisions of thermal modernization of enclosing designs developed by us provides that the estimation on criteria which have subcriteria is defined as the sum of estimations of subcriteria. The evaluation of the criteria is carried out on a five-point scale. The optimal technical solution is the solution that received the highest score on the total.